A client/server approach to telemedicine. - Vaughan, B. J. (American Medical Informatics Association, 1995)
This paper describes the Medical College of Ohio's efforts in developing a client/server telemedicine system. Telemedicine vastly improves the ability of a medical center physician or specialist to interactively consult with a physician at a remote health care facility. The patient receives attention more quickly, he and his family do not need to travel long distances to obtain specialists' services, and the primary care physician can be involved in diagnosis and developing a treatment program [1, 2]. Telemedicine consultations are designed to improve access to health services in underserved urban and rural communities and reduce isolation of rural practitioners [3].